COC refuses to move forward on priority vaccination for athletes (The Canadian, 2021)
The Canadian Olympic Committee has remained cautious about whether to prioritize Olympic athletes during the mass COVID-19 vaccination campaign to be held in Canada this year, distancing itself from the words of the influential Canadian member of the Committee international Olympic Dick Pound.